A meta-analysis of the relationship between the RPE and well-being in adolescent athletes: the critical moderating role of well-being dimensions - Gu, Y.; Liu, Y.; Cheng, L. (Frontiers in Psychology, 2025)
Introduction: The relationship between the Rating of Perceived Exertion (RPE) and well-being in adolescent athletes is controversial, complicating effective athlete monitoring. This meta-analysis aimed to clarify this relationship and investigate the critical moderating role of well-being dimensions.